(NkRATKIJ KURS TEORETI^ESKOJ MEHANIKI (B:s (Nu^EBNOE POSOBIE (B/s - (NtARG(B, (NsEMEN mIHAJLOWI^s ((NmOSKWA (B:s (NnAUKA (B,s, 1974)
(NpREDM(B. (NUKAZ(B.: (NS(B. 473-478s
Keywords: (NmEHANIKA TEORETI^ESKAQs